Screening for Phenols from Few Medicinal Plants - Seetharam, Y.N.; Srinivas Murthy, N. (Asian Journal of Chemistry, 2010)
Phenols are very important, biologically active constituents. known for their antifungal and antiallergic properties. In the present study well known medicinal plants used in various systems of medicine to cure different ailments were screened qualitatively by using chromatographic method and estimated quantitatively by spectrophotometric studies.